Introduction to the Special Issue - Faith E. Crampton; David C. Thompson (Educational Considerations, 2011)
We are pleased to share with you this special issue revisiting the research on the relationship between class size and student achievement, along with its implications for education policymakers and practitioners. For over half a century, researchers have struggled to identify those variables that contribute in significant ways to students’ academic success, and the resulting, voluminous literature is rife with contradictory results. At the same time, the positive results of class size research, which is part of the body of “production function” analysis, has received broad acceptance by policymakers, parents, and practitioners who believe “smaller is better.”
Keywords: class size; student achievement